Smoking impairs molecular response, and reduces overall survival in patients with chronic myeloproliferative neoplasms: A retrospective cohort study. (10th November 2020) - Sørensen, Anders Lindholm; Knudsen, Trine A.; Skov, Vibe; Kjær, Lasse; Holm, Nanna; Ellervik, Christina; Hasselbalch, Hans Carl
Summary: The effects of smoking on the molecular response (MR) and overall survival (OS) in patients with chronic myeloproliferative neoplasms (MPNs) have not been investigated before. We analysed a historical cohort of 498 consecutive patients diagnosed with MPNs. Moreover, we analysed a subgroup of 270 consecutive patients with MPNs with > 1 measurement of the JAK2 V617F variant allele frequency. The data were analysed using Kaplan–Meier plots and Cox regression analysis, along with linear regression models. In all patients, the rate of MR was significantly higher in never‐smokers compared with current smokers in the univariate model (HR, 1·9; 95% CI, 1·1–3·3; P  = 0·033) and the multivariate model (HR, 1·9; 95% CI, 1·1–3·5; P  = 0·029). Similar findings were observed with different cut‐off values for a partial MR. A subgroup analysis including only interferon‐α2‐treated patients showed similar results. In multivariate analyses, the OS was significantly better for never‐smokers (HR, 0·46; 95% CI, 0·29–0·75; P  = 0·002) than current smokers. The differences were more pronounced in the pegylated interferon‐α2‐treated patients. However, no significant interaction of interferon‐α2 treatment was observed. In conclusion, we found that tobacco smoking reduced the rate of MR and OS in patients with MPNs. Cessation of smoking should be encouraged.